Exercise Prescription in Polycystic Ovary Syndrome: A Review of Recent Findings - Rendaszka, Katarzyna; Chmura, Katarzyna; Zimnoch, Barbara; Kowalska, Katarzyna; Pyziołek, Marta; Bonarska, Marta; Stróżna, Małgorzata; Najbar, Joanna Monika; Kwaśniewska, Paulina (Quality in Sport, 2025)
Introduction: Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder affecting women. It is characterized by irregular menstrual cycles, hyperandrogenism and insulin resistance. PCOS is associated with increased cardiometabolic risk and psychological burden. Lifestyle modification, particularly exercise, is a cornerstone of non-pharmacological treatment. This review summarizes recent findings (2022–2025) on the impact of different exercise modalities including high-intensity interval training (HIIT), moderate-intensity continuous training (MICT), aerobic, resistance, combined, Pilates, and yoga on metabolic, hormonal, reproductive, and psychological outcomes in women with PCOS. Aim of study: The aim of this study is to determine whether any specific exercise modality provides greater clinical benefits than others in women with PCOS. Material and methods: The review was conducted using two electronic databases: PubMed and Google Scholar. Searches were performed using the following keywords in various combinations: polycystic ovary syndrome, PCOS, exercise, physical activity, high-intensity interval training, moderate-intensity continuous training, aerobic training, resistance training, combined training, yoga, and Pilates. Conclusions: Evidence indicates that all types of exercise confer benefits, though no single modality demonstrates clear superiority. Overall, exercise prescriptions should be individualized, patient-centered, and aligned with personal preferences and capabilities to ensure long-term adherence and maximize therapeutic impact. Further research involving larger cohorts and longer intervention periods is needed to identify the most effective exercise strategies for optimizing clinical outcomes.